PENGARUH GAYA KOMUNIKASI PEMIMPIN TERHADAP MOTIVASI KERJA KARYAWAN (Studi Korelasi Pada Pegawai Aparatur Sipil Negara di Sespim Lemdiklat Polri) - Yulia Primadhianti, - (2020)
Abstract. An employee has an important role in the effectiveness of an organization. Therefore, if an employee feels discouraged while doing their job, productivity and effectiveness in the company will become severely hampered. This can be helped by the absence of a competent leader. The leader will be able to influence their subordinates on their own way to achieve the organization's goals. That ability is called the leader's communication style. Each leader has a different communication style in running their organization. However, the right communication style will make excellent cooperation between the leader and their subordinates. The purpose of this research was to find out if there is an influence on the level of leader communication style to the level of employee work motivation. This study used a correlational quantitative method with questionnaires as data collection tool and was distributed to 130 respondents who are State Civil Apparatus (ASN) in Sespim Lemdiklat Polri. For data analysis techniques, researcher used a descriptive statistics and multiple regression analysis. The results of this study indicated that work motivation is significantly influenced by Emotive Style, Director Style, Supportive Style and Reflective style which is an aspect of the leader's communication style with a determinant coefficient value of 0.402 and a strong correlation rate. Keywords: Leader Communication Style, State Civil Apparatus (ASN), Organizational Communication, Work Motivation.